Efficacy and safety of single-session radiofrequency ablation for benign thyroid nodules of different sizes: a retrospective study - Wei-Che Lin (International Journal of Hyperthermia, 2020)
Purpose To compare the effectiveness of radiofrequency ablation (RFA) for benign thyroid nodules (BTNs) among groups presenting with different nodule volumes. Materials and methods This retrospective study evaluated 186 patients with BTNs who underwent ultrasound guided RFA treatment. The BTNs were categorized into small (≤10 ml); medium (10-30 ml); and large (>30 ml) according to the initial volume of BTNs before ablation. The RFA procedures were performed using the moving shot technique. The volume reduction ratio (VRR) of each nodule, cosmetic score, symptomatic score, and complications were analyzed at 1, 3, and 6 months after RFA treatment and the three groups compared. Results At 1-month follow-up, the large nodules group showed significantly greater VRR compared to the other two groups (small, 31.88% ± 37.91; medium, 38.9% ± 19.18; large, 48.7% ± 20.43, p = .03). At 6-month follow-up, there was no significant difference of VRR among the three groups (small, 74.6% ± 20.92; medium, 68.1% ± 17.07; large, 75.0% ± 11.88). The most common presented complication was temporary vocal palsy (6 patients; small, n = 1; medium, n = 1; large, n = 3). Additionally, one skin burn, one hematoma, and one nodular rupture of BTNs occurred after the procedures. The complication rate of the large nodules group was highest among the three groups and showed a considerable difference (8 patients; small, n = 1, 2.1%; medium, n = 2, 4.5%; large, n = 5, 11.4%, p = .061). Conclusions RFA was confirmed as effective in patients with large thyroid nodule (>30ml), with therapeutic efficacy similar to patients with smaller thyroid nodules.